Follow-Up Investigation of 41 Children After Metallic Airway Stent Implantation: An 8-Year Experience - Wang, Meng; Zhu, Bin; Xu, Xuan (Frontiers in Pediatrics, 2020)
Objective: To report the 8-year follow-up outcomes, treatment of complications, and prognosis in children with congenital tracheal stenosis after metal airway stent implantation. Methods: Retrospective analysis was performed on the clinical records of children who had airway stents placed between May 20, 2011 and May 31, 2016, and on their follow-up records collected by November 31, 2019. Results: During the 8 years follow-up, 41 children underwent airway stenting under flexible bronchoscopy and participated in the follow-up investigation. There were 26 cases with left main bronchus (LMB) stenosis (63.4%), 16 cases with congenital tracheal stenosis (CTS, 39.0%), 12 cases with right main bronchus (RMB) stenosis (29.3%), and 1 case of subglottic stenosis (2.4%). A total of 76 stents were implanted, and 21 patients died after implantation. There were 34 children (82.9%) with congenital heart disease (CHD), while other diseases accounted for less than 5%. Among children with CHD and those with other conditions, the number of death cases was 19 and 9, respectively; no significant differences were observed between the two groups (P>0.05). The most frequent complications were increased airway secretion (75.8%), stent deformation (66.7%), and granulation tissue hyperplasia (60.6%). The airway stenosis (45.5%) and stent migration (12.1%) occurred at a moderate rate. The less common complications were airway softening (6.1%), and stent fracture (6.1%). Conclusions: The placement and removal of the metal stent are convenient and quick procedures that can relieve the symptoms of dyspnea caused by airway stenosis in the case of an emergency. After stent implantation, the primary disease should be actively treated, and the stent should be removed as soon as possible after the cause of airway stenosis is successfully removed. Larger stents are more likely to cause complications; thus, a good follow-up system should be established to timely address all the complications.